Hubungan Persepsi Manfaat terhadap Kesadaran Kesehatan Pengguna Wearable Device di Kota Banda Aceh - Fitri, Raihanil; Dilla Santi, Tahara; Rani, Hafnidar A. (Perilaku dan Promosi Kesehatan : Indonesian Journal of Health Promotion and Behavior, 2025)
Background. Wearable devices are portable technologies designed to be worn directly on the body and capable of collecting and analyzing data related to various aspects of a user's health. Aim. This study aims to analyze the influence of perceived benefits on users' health awareness among wearable device users in Banda Aceh City. Aim. This study aims to analyze association of perceived benefits on users' health awareness among wearable device users in Banda Aceh City. Method. This research applied a descriptive quantitative design with a cross-sectional approach. Data were collected using a questionnaire from 106 active wearable device users engaging in physical activity at Harapan Bangsa Stadium and Blang Padang Field, Banda Aceh. Respondents were selected using purposive sampling. Data were analyzed using logistic regression with STATA17.0. Result. The results indicated that the type of wearable device did not significantly affect users’ health awareness (OR = 0.766; P = 0.562). However, device features (OR = 55.5; P = 0.000), comfort in use (OR = 46.6; P = 0.000), and usage frequency (OR = 4.06; P = 0.004) showed a significanteffect. Conclusion. The conclusion is that the features, comfort, and frequency of use of wearable devices have a significant impact on users' health awareness, whereas the type of device does not.